Barkeria uruapani (Laeliinae, Epidendroideae, Orchidaceae), a new species from western Mexico - León-Peralta, Cekouat E.; Valdez-Partida, Julio; Pérez-García, Eduardo A. (Phytotaxa, 2021)
Barkeria uruapani, a new orchid species endemic to Michoacán, Mexico, is described and illustrated. Information on its distribution, habitat and conservation status is provided. The new species is also compared with B. barkeriola and B. uniflora, and an updated key to all Barkeria species is included. Diagnostic features of B. uruapani include the branching inflorescences with simultaneous anthesis, the elliptical-obovate lip with a large magenta spot, the revolute wings of the column and the lateral sepals forming an obtuse angle.